2022
DOI: 10.4103/ijn.ijn_258_21
|View full text |Cite
|
Sign up to set email alerts
|

Childhood steroid-resistant nephrotic syndrome: Long-term outcomes from a Tertiary Care Center

Abstract: Introduction: Steroid-resistant nephrotic syndrome (SRNS) is a rare condition that accounts for about 10% to 20% of all nephrotic syndromes in children. While calcineurin inhibitors induce remission in the majority, the data on long-term outcomes are limited. This retrospective study aimed to look at the clinical profile, biopsy findings, and long-term treatment outcomes in children with SRNS. Methods: The records of all children (1–18 years) with SRNS with biopsy findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[16] A Retrospective study from our centre in 92 SRNS patients showed that 31.9% had initial resistance and 68.1% late resistance. [17] A higher proportion of late resistance in the present study could be due to the inclusion of patients in disease remission and remission rates are better in late compared to initial resistance. Most patients with SRNS course were treated with either of the CNI's; cyclosporine and tacrolimus were used for more than 2 years in 40% and 20% of SRNS patients respectively and 28% were administered rituximab additionally during the treatment course.…”
Section: Discussionmentioning
confidence: 61%
“…[16] A Retrospective study from our centre in 92 SRNS patients showed that 31.9% had initial resistance and 68.1% late resistance. [17] A higher proportion of late resistance in the present study could be due to the inclusion of patients in disease remission and remission rates are better in late compared to initial resistance. Most patients with SRNS course were treated with either of the CNI's; cyclosporine and tacrolimus were used for more than 2 years in 40% and 20% of SRNS patients respectively and 28% were administered rituximab additionally during the treatment course.…”
Section: Discussionmentioning
confidence: 61%
“…This might be due to patients with decreased urine output having decreased renal blood ow and reduced peri-renal capillaries, which in turn results in a poor outcome for NS. However, the nding was in contravention of the study conducted in India (43). This discrepancy might be due to differences in sample size, genetic, and ethnic differences, age variation (up to 18 years), and study design (follow-up study).…”
Section: Discussionmentioning
confidence: 79%
“…Approximately 1020% of them have steroid resistant nephrotic syndrome (SRNS). [2][3][4] The patient who has no urinary remission within four weeks of prednisolone therapy 60 mg/m 2 /day followed by three intravenous pulses of methylprednisolone is termed SRNS. 5 Response to steroids varies due to various pathophysiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%